The influence of flaxseed gum on the microrheological properties and physicochemical stability of whey protein stabilized β-carotene emulsions. Issue 1 (11th January 2017) - Xu, Duoxia; Qi, Yameng; Wang, Xu; Li, Xin; Wang, Shaojia; Cao, Yanping; Wang, Chengtao; Sun, Baoguo; Decker, Eric; Panya, Atikorn
Abstract : The impact of flaxseed gum (FG) on the microrheological properties and physicochemical stability of whey protein isolate (WPI) stabilized β-carotene emulsions at pH 3.0 was studied. Abstract : The impact of flaxseed gum (FG) on the microrheological properties and physicochemical stability of whey protein isolate (WPI) stabilized β-carotene emulsions at pH 3.0 was studied. A layer-by-layer electrostatic deposition method was used to prepare multilayered β-carotene emulsions with interfacial membranes consisting of WPI and FG. The microrheological behavior of the multilayered β-carotene emulsions was measured through the diffusive wave spectroscopy technique. WPI alone and WPI–FG (concentration of FG = 0.1, 0.2, 0.3 wt%) stabilized β-carotene emulsions were purely viscous giving a mean square displacement that scaled linearly with decorrelation time ( τ ). The presence of 0.01, 0.02, and 0.05 wt% FG in the WPI-stabilized emulsions caused them to exhibit viscoelastic properties. Meanwhile, the increase in τ reflected the increase in the length scale of connectivity in the emulsions until a "cluster" was formed and the droplets were not free to move due to droplet–network interaction. The apparent increase in the macroscopic viscosity and elasticity index and decrease in the solid lipid balance and fluidity index of emulsions with lower concentrations (0.01, 0.02, 0.05 wt%) of FG indicated that the bridging flocculation of FG had a much more appreciable influence on the microrheological properties than depletion flocculation (higher concentrations, 0.1, 0.2, 0.3 wt%). Droplet size, zeta-potential, and transmission profiles using the centrifugal sedimentation technique and β-carotene degradation during storage were also characterized. With the addition of FG, the zeta-potential of WPI coated β-carotene droplets decreased from positive to negative, and an increase in the apparent droplet size was also noted. LUMISizer analysis exhibited an improvement in physical stability with the addition of 0.1 wt% FG. FG also helped to chemically stabilize the WPI emulsions against β-carotene degradation mainly by slowing down the mobility of the droplets.